2017
DOI: 10.4103/ijem.ijem_196_17
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference as a marker of overweight and obesity and cutoff values for Bangladeshi adults

Abstract: Objective:There are several methods of assessing overweight and obesity. Several studies conducted in different populations indicate that neck circumference (NC) can be used as a simple measure of overweight and obesity. This study was conducted to evaluate NC as a marker of overweight and obesity and to determine respective cutoff values for Bangladeshi male and female participants.Research Design/Materials and Methods:This cross-sectional observational study was conducted with during July 2013–June 2014 amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 11 publications
5
22
2
Order By: Relevance
“…The differences are not unexpected given the relationship between NC with age, BMI and WC. Consistent with previous studies men had a higher mean NC [14,18,21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The differences are not unexpected given the relationship between NC with age, BMI and WC. Consistent with previous studies men had a higher mean NC [14,18,21].…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted among the Turks [11,13] and Saudi Arabs [14] revealed that NC had positive correlation with indices of general and central obesity. Similar studies among the Chinese [15][16][17], Indians [18,19], Indonesians [20], and other Asian populations [21], also confirmed the positive association between NC with established anthropometric indices and cardiovascular risk factors. Specifically, Fan et al, [22] examined the relationship between NC and arterial hypertension, and found that NC predicted blood pressure, independent of other anthropometric indices.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…NC provide high values in prediction of distribution of upper-body subcutaneous, is valid marker and the data collection is simple to execute [5256]. BMI and others anthropometric indicators have long been suggested of defining the overweight and obesity of person [57].…”
Section: Discussionmentioning
confidence: 99%
“…The study proposed cutoffs of 33.5 cm among the females and 37 cm among the males with high value of speci city and sensitivity. Among Bangladesh adults, NC was found to have the ability to distinguish overweight and obese adults from their counterparts [11]. Findings from a study that included 864 children and adolescents from Iran, showed that NC was signi cantly correlated with BMI, WC and Mid upper arm circumference (MUAC) [14].…”
Section: Introductionmentioning
confidence: 99%